Biosynthesis of Levan by Halomonas elongata 153B: Optimization for Enhanced Production and Potential Biological Activities for Pharmaceutical Field - TOKSOY ÖNER, EBRU (My University, 2022)
Halophilic organisms are a novel attractive option as cell factories for the production of industrially valuable bioproducts. Halomonas elongata is the cell factory of choice for ectoine production, but its levan production has not been well researched. Based on this scientifc motivation, in this study, we evaluated the chemical and biological properties of levan produced by the halophilic extremophile Halomonas elongata 153B (HeL). First, the central composite design was used to determine the optimal process variables for maximum levan biosynthesis. Then, the levan produced from HeL was purifed, quantifed, and chemically characterized with FTIR, 1 H-NMR, and GPC analyses. This was followed by antioxidant, anti-infammatory, antibioflm, and antimicrobial activity tests to assess its biological activities as well as a cytotoxcity assay. Maximum levan yields of 5.13±0.38 g/L were achieved after dialysis at the optimum levels of process variables. The 1 H-NMR spectrum of HeL revealed characteristic signals. It showed a strong antioxidant activity of 67.88% and the best radical scavenger. At a concentration of 400 µg/mL, HeL showed the most anti-infammatory efcacy. Also, at all indicated concentrations (250, 500, 750, and 1000 μg/mL) HeL, acted against bioflms formed by Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 11778, Candida albicans ATCC 10231. Furthermore, HeL displayed antimicrobial activities against all strains tested. Finally, HeL showed high Cell viability in all dosages and no cytotoxicity was observed. In light of these results, HeL may have high potential in the medical, pharmaceutical and dermo-cosmetics industries.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, ÇEVRE; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, ENVIRONMENTAL; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Çevre Mühendisliği; Fizik Bilimleri; Polimerler ve Plastikler; Malzeme Kimyası; Environmental Engineering; Physical Sciences; Polymers and Plastics; Materials Chemistry; Biological activity; Cytotoxicity; Halomonas elongata; Halophilic; Levan; Response surface methodology; Halophilic; Levan; Halomonas elongata; Response surface methodology; Biological activity; Cytotoxicity